2021
DOI: 10.1155/2021/5868326
|View full text |Cite
|
Sign up to set email alerts
|

New Fractional Hermite–Hadamard–Mercer Inequalities for Harmonically Convex Function

Abstract: In 2003, Mercer presented an interesting variation of Jensen’s inequality called Jensen–Mercer inequality for convex function. In the present paper, by employing harmonically convex function, we introduce analogous versions of Hermite–Hadamard inequalities of the Jensen–Mercer type via fractional integrals. As a result, we introduce several related fractional inequalities connected with the right and left differences of obtained new inequalities for differentiable harmonically convex mappings. As an applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Kara et al [15] used the convexity for interval-valued functions and demonstrated fractional Hermite-Hadamard-Mercertype inequalities. The authors applied the concept of harmonically convex functions and established Hermite-Hadamard-Mercer inequalities with their estimates in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Kara et al [15] used the convexity for interval-valued functions and demonstrated fractional Hermite-Hadamard-Mercertype inequalities. The authors applied the concept of harmonically convex functions and established Hermite-Hadamard-Mercer inequalities with their estimates in [16].…”
Section: Introductionmentioning
confidence: 99%
“…This inequality has been generalized by many researchers, taking into account various aspects such as general convexity and fractional operators. For Hermite-Hadamard-Mercer type results, see [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate and improve the error bounds for some well‐known integral inequalities, including the trapezoidal, midpoint, and Ostrowski‐type inequalities, inequality () has been established and generalized in numerous ways for various classes of convex functions [3–28]. Dragomir and Agarwal [11] established some inequalities of the trapezoidal type for differentiable convex functions by taking into consideration the above inequality.…”
Section: Introductionmentioning
confidence: 99%